Mechanism of wetting–induced deformation and failure of unsaturated soils. (9th February 2022) - Komolvilas, Veerayut; Kikumoto, Mamoru; Kyokawa, Hiroyuki
Abstract: The mechanisms of hydraulic collapse (wetting‐induced deformation) are studied through a series of simulations using a model for unsaturated soils. The model is a critical state soil model extended for unsaturated soils using Bishop's effective stress tensor, the state boundary surface (SBS) moving with the change in the degree of saturation, and a rational soil‐water characteristic curve that takes account of density and hydraulic hysteresis. Comparisons with published experimental data validate the proposed model. The simulation results show that the model adequately captures the hydraulic collapse behavior under both isotropic and anisotropic stress conditions. The effects of density, mean net stress, and deviatoric stress on the hydraulic collapse behavior are further investigated through a parametric calculation, and the mechanics of the wetting–induced instability are discussed. The effects of suction history, namely repeated wetting and drying cycles, on the deformation and failure, are also presented. The proposed model provides a validated method for modeling hydromechanical collapse in unsaturated soil and provides a better understanding of the mechanisms involved.